2020
DOI: 10.2147/nss.s234310
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychomotor Performance in Patients with Obstructive Sleep Apnea Syndrome</p>

Abstract: Purpose: Determinants of obstructive sleep apnea (OSA) are hypoxemia and hypercapnia, as well as (micro) arousals from sleep, resulting in chronic sleep fragmentation, sleep deprivation, and excessive daytime sleepiness (EDS). All of the above-mentioned factors might contribute to psychomotor impairment seen in OSA patients. Additionally, this study aimed to assess the contribution of BMI, age, EDS assessed with Epworth sleepiness scale (ESS), and severity of OSA assessed with apnea-hypopnea index (AHI) to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Kalcina et al reported an impaired speed of perception, convergent, and operative thinking in untreated OSA patients compared to the control group measured by CRD-series test (CRD5.2 ± 1.8 vs. 4.5 ± 1.33, p < 0.01; CRD. 41: OSA 25.1 ± 17.99 vs. 20.3 ± 11.1 p < 0.05; CRD11: OSA 38.8 ± 19.3 vs. 33.3 ± 14.1, p < 0.05) [ 25 ]. Decreasing stability of performance toward the end of the tests, assessed with end ballast (EB) measures of the CRD tests, indicated that OSA patients obtain considerably slower toward the end of tasks than control participants.…”
Section: Resultsmentioning
confidence: 99%
“…Kalcina et al reported an impaired speed of perception, convergent, and operative thinking in untreated OSA patients compared to the control group measured by CRD-series test (CRD5.2 ± 1.8 vs. 4.5 ± 1.33, p < 0.01; CRD. 41: OSA 25.1 ± 17.99 vs. 20.3 ± 11.1 p < 0.05; CRD11: OSA 38.8 ± 19.3 vs. 33.3 ± 14.1, p < 0.05) [ 25 ]. Decreasing stability of performance toward the end of the tests, assessed with end ballast (EB) measures of the CRD tests, indicated that OSA patients obtain considerably slower toward the end of tasks than control participants.…”
Section: Resultsmentioning
confidence: 99%
“…Giora observed an overall perceptual deficit consisting in OSA patients invested by means of a visual search task ( Giora et al, 2017 ). Lusic confirmed that individauls with severe OSA had impaired speed of perception, convergent, and operative thinking ( Kalcina et al, 2020 ).…”
Section: Introductionmentioning
confidence: 88%
“…In general, the screening efficiency of these questionnaires is not ideal. Some OSA patients also have chronic daytime hypercapnia [ 5 ]. To maintain the acid–base balance in the body, the kidney reduces the excretion of HCO 3 − , leading to an increase in arterial blood HCO 3 − .…”
Section: Introductionmentioning
confidence: 99%